Akibat Hukum Tidak Dilaksanakannya Tanggung Jawab Perusahaan Sekuritas Sebagai Penjamin Emisi Efek (Underwriter) Dalam Mewujudkan Prinsip Keterbukaan Di Pasar Modal - Wawan Susilo (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Securities Companies (Securities) are parties that obtain permission from the Financial Services Authority to carry out activities, one of which is as an Underwriter. The Underwriter has an important role to carry out a Public Offering in the interest of the Issuer by entering into an Underwriting agreement and is responsible for the correctness of the material information on the registration statement and the contents of the prospectus in the context of a public offering based on laws and regulations in the capital market and its implementing regulations. Whereas the responsibility of a Securities Company as an Underwriter (Underwriter) in realizing the Principle of Openness in the Capital Market is responsibility for the Underwriting Agreement, responsibility for the correctness of Material Information in the Registration Statement, responsibility for the Correctness of Material Information in the Prospectus, and responsibility on Non Public Information (information not available to the public). The legal consequences of non-implementation of the Disclosure Principle by Securities Companies as Underwriters (Underwriters), namely the occurrence of violations that will result in sanctions. The sanctions are in the form of administrative sanctions and criminal sanctions. Civil sanctions may also be imposed if the violation committed by the Underwriter causes losses to investors or other parties who have a relationship with the Underwriter. Keywords: Legal Consequences, Responsibility, Underwriters, Disclosure, Capital Markets.